The Project Music for Everybody in the Context of Continuous Education in Yakutia - Gorbunova, Irina B. (2020)
In 2013, President of the Republic of Sakha (Yakutia) Mikhail Nikolaev announced the launch of the republican project Music for Everybody. The organizers of this project –– the Ministry of Education and the Ministry of Culture and Spirituality of the republic –– have set the goal to help all children learn one classical musical instrument by their graduation from general education school. For this purpose, the ministries signed an agreement on joint work in order to promulgate the project that was developed and organized by scientists, musicians, and teachers. In 2015, the Music Faculty of the Yakutsk Gogolev Pedagogical College was appointed as a project coordinator for providing methodological assistance during the implementation of this program. Against this backdrop, the present article discusses the main coordinating aspects and elements of the methodological support of Music for Everybody, which are aimed at consolidating the efforts of the music teachers of Yakutia. In this regard, modern musical computer technologies are increasingly playing a significant role in preparation of the key components of the educational process’s methodological support within the context of project implementation. The application of such technologies facilitates the preservation of the cultural features and national colors of ethnic groups living in the Republic of Sakha (Yakutia), while also making it possible to broadcast the most salient elements of the multinational cultural traditions of the republic’s indigenous ethnic groups.